Correlation between saliva IgA level and T cell CD4+ in HIV/AIDS patients - Sufiawati, Irna; Sasanti, Harum; Djauzi, Samsuridjal (Padjadjaran Journal of Dentistry, 2007)
Background: HIV infection appears to have direct effects on oral mucosal immunity, cellular and humoral. Antibody secretion, especially salivary immunoglobulin A (IgA), is a useful indicator of mucosal immune function. This immune system component is recognized as an important first-line of defence against pathogens which colonize and invade mucosal surfaces in the oral cavity. Objectives: The purpose of this study was to investigate salivary IgA levels and to determine its correlation with CD4+ T-cell counts among HIV-infected patients in Pokdisus AIDS Cipto Mangunkusomo Hospital Jakarta. Methods: The design study was using a cross-sectional study. Whole paraffin-wax-stimulated saliva was collected from 103 HIV-infected patients and 30 healthy individuals. Saliva was collected using the spitting method. Salivary IgA levels were determined by the immunoturbidimetry method using the Behring Turbitimer Analyser. CD4+ T-cell counts were analyzed by flow cytometry. Results: Salivary IgA levels were 141.55 ± 83.23 (HIV group) and 97.24 ± 38.25 (healthy individuals). The Mann-Whitney U test showed salivary IgA levels were significantly higher in HIV/AIDS subjects compared with healthy individuals (p<0.1). Most of the subject has severe immunosuppression with CD4+ T-cell counts <200 cell/mm.3 Pearson’s correlation test between CD4+ T-cell counts and salivary IgA levels showed no significant correlation (r= 0.06, p>0.1). Conclusion: This study indicates that total salivary IgA levels were significantly higher in the HIV-infected patients compared to control, and salivary IgA level seems not to be related significantly to CD4+ T-cell counts.